Expression of COBLL1 encoding novel ROR1 binding partner is robust predictor of survival in chronic lymphocytic leukemia - Plešingerová, Hana; Janovská, Pavlína; Mishra, Archana; Smyčková, Lucie; Poppová, Lucie; Libra, Antonín; Plevová, Karla; Ovesná, Petra; Radová, Lenka; Doubek, Michael; Pavlová, Šárka; Pospíšilová, Šárka; et al. (Haematologica, 2018)
Chronic lymphocytic leukemia is a disease with up-regulated expression of the transmembrane tyrosine-protein kinase ROR1, a member of the Wnt/planar cell polarity pathway. In this study, we identified COBLL1 as a novel interaction partner of ROR1. COBLL1 shows clear bimodal expression with high levels in chronic lymphocytic leukemia patients with mutated IGHV and approximately 30% of chronic lymphocytic leukemia patients with unmutated IGHV. In the remaining 70% of chronic lymphocytic leukemia patients with unmutated IGHV, COBLL1 expression is low. Importantly, chronic lymphocytic leukemia patients with unmutated IGHV and high COBLL1 have an unfavorable disease course with short overall survival and time to second treatment. COBLL1 serves as an independent molecular marker for overall survival in chronic lymphocytic leukemia patients with unmutated IGHV. In addition, chronic lymphocytic leukemia patients with unmutated IGHV and high COBLL1 show impaired motility and chemotaxis towards CCL19 and CXCL12 as well as enhanced B-cell receptor signaling pathway activation demonstrated by increased PLCγ2 and SYK phosphorylation after IgM stimulation. COBLL1 expression also changes during B-cell maturation in non-malignant secondary lymphoid tissue with a higher expression in germinal center B cells than naïve and memory B cells. Our data thus suggest COBLL1 involvement not only in chronic lymphocytic leukemia but also in B-cell development. In summary, we show that expression of COBLL1, encoding novel ROR1-binding partner, defines chronic lymphocytic leukemia subgroups with a distinct response to microenvironmental stimuli, and independently predicts survival of chronic lymphocytic leukemia with unmutated IGHV.
Keywords: mutace; Immunoglobulin Variable Region; transkripční faktory; Immunoglobulin Heavy Chains; Leukemia, Lymphocytic, Chronic, B-Cell; vazba proteinů; lidé; Survival Analysis; Transcription Factors; Mutation; těžké řetězce imunoglobulinů; Wnt Signaling Pathway; prognóza; sirotčí receptory podobné receptoru tyrosinkinasy; pohyb buněk; polarita buněk; signální dráha Wnt; Cell Polarity; Prognosis; analýza přežití; variabilní oblast imunoglobulinu; Cell Movement; Protein Binding; Receptor Tyrosine Kinase-like Orphan Receptors; chronická lymfatická leukemie; Humans